INKONSTITUSIONALITAS PEMBENTUKAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG NO. 2 TAHUN 2022 BERDASARKAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 91/PUU-XVIII/2020: Inconstitutionality of Formation of Government Regulation Substituting Law No. 2/2022 Based on Constitutional Court Decision Number 91/PUU-XVIII/2020 - Nyimas Reysandra Kinnary; Ali Rido (Reformasi Hukum Trisakti, 2025)
This study discusses the issuance of Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation, which sparked debates regarding the fulfillment of the "compelling urgency" requirement based on Article 22 of the 1945 Constitution of the Republic of Indonesia and Constitutional Court Decision Number 138/PUU-VII/2009. The research focuses on the urgency of the regulation's issuance and the potential for a legal vacuum, the research question in this study is whether the issuance of Government Regulation in Lieu of Law (Perppu) Number 2 of 2022 concerning Job Creation can be considered a deviation from the proper legislative mechanism for amending Law Number 11 of 2020?   The findings indicate that the issuance of the Government Regulation in Lieu of Law did not meet constitutional requirements, as the Job Creation Law remained in effect despite being conditionally unconstitutional. The government is considered to have neglected its obligation to revise the law through legislative mechanisms. This study employs a normative juridical approach with a descriptive-analytical method. In conclusion, the issuance of this regulation was not based on an urgent situation and has led to legal uncertainty.